The Prometheus Project - Ryan Watts (EXARC, 2014)
The Prometheus Project was an experimental archaeological investigation carried out at Butser Ancient Farm, Hampshire, England, into prehistoric logboat building techniques. The project focused on exploring the use of fire in building logboats, a common method of construction in historical cultures but one over looked in prehistory. A 2.5 m long oak logboat was built using replica Bronze Age tools and fire to see if any evidence for the use of fire was left in the completed craft. The project was funded by HLF and CBA challenge funding and Butser Ancient Farm.